Improving social acceptance for carbon taxation in South Korea - Yeochang Yoon (KDI Journal of Economic Policy, 2023)
Carbon pricing is in the spotlight as an economically efficient policy to limit global warming and reduce greenhouse gas emissions. We examine how policymakers can improve social acceptance of a carbon tax, which is the main obstacle in implementing the policy. We conduct a survey experiment to analyze this topic and adopt two different interventions focusing on the use of revenue from a carbon tax and types of information to be provided. Regarding revenue use, we consider 1) tax reductions, 2) lump-sum transfers, and 3) green project investments. For information types, we focus on 1) the economic value of a carbon tax, and 2) the environmental value of a carbon tax. We find that lump-sum transfers have negative impacts on social acceptance of a carbon tax. For those who perceive climate change as a serious issue, moreover, both lump-sum transfers and tax reductions have negative impacts on acceptability. Regardless of the type of information provided, on the other hand, the social acceptance of a carbon tax is increased after the provision of information. Furthermore, the impact of information provision on the social acceptance interacts with the revenue use impacts. When the revenue use and the type of information are consistent with the aim of the policy, the effects of these strategies can be amplified.
Keywords: Q54; C99; 330; Carbon Tax; Carbon Pricing Mechanism; Climate Change; Policy Design